Productivity effect of minimum wage in the manufacturing sector of Malaysia - Tajuddin, Sheikh Ahmad Faiz Sheikh Ahmad; Muhamad, Suriyani; Hasan, Fauziah Abu; Sulaiman, Nor Fatimah Che (Asian Journal of Economic Modelling, 2023)
This study measured the effectiveness of Malaysia’s minimum wage by assessing the effect of minimum wage on productivity in the Malaysian manufacturing sector. Panel data covering a 10-year period were collected from 297 manufacturing firms in Peninsular Malaysia that were registered with the Federation of Malaysian Manufacturers (FMM) and analysed using static panel data regression to examine the effect of minimum wage on productivity. Panel data analysis revealed that the study’s random effect model (REM) was the best model to describe the relationship between the minimum wage and productivity. The study found that the minimum wage improved labour productivity. Therefore, the minimum wage policy that was introduced in Malaysia under the Minimum Wage Order 2012 increased firms’ productivity. Increasing workers’ wages motivated them to be more productive. This study’s results are useful in highlighting to regulators, policymakers, manufacturing associations, employers, and workers the effects of the minimum wage. The implications of the findings will help improve the national minimum wage policy.